The Basis of Minimum Wages Determination for Worker in Indonesia Positive Law and Sharia - Julaicha, Siti; Wijayanti, Asri; Sahid, Mualimin Mochammad (Universitas Muhammadiyah Surabaya, 2022)
This study aims to analyze the basis of wages determination for workers in the perspective of positive law and Sharia. The Labor Act prohibits employers from paying wages below the minimum wage. The threat of criminal sanctions for small employers who cannot afford to pay and there is no sanction for large employers to pay wages to all workers without any differences in work tenure. This research is a normative juridical with statute approach. The results of this study showed that there were differences in parameters in the determination of workers' wages based on the Manpower Act, and sharia principles. The minimum wage parameter based on the Labor Law is the need for a decent living for single workers. While Sharia parameters are more flexible. Determination of wages based on agreement according to the conditions of the parties and provide benefits. In conclusion, the determination of wages based on sharia principles is closer to the sense of fairness for the parties. The recommendation is to revise the parameters for determining the minimum wageKeywords: benefit; minimum wage; sharia; fairness.